2011
DOI: 10.5251/abjna.2011.2.3.512.521
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of Indol Acitic Acid (IAA) and Gebirilic acid (GA3) as well as interaction effect on growth yield and some physiological compositions of Triticum plant grown under salinity conditions

Abstract: The present study aimed to investigate the effect of spraying with IAA and GA3 and the interaction between them on improvement the growth, yield and some biochemical and physiological characteristics of wheat plant (Triticum durum serf Triticum aestivum) of two cultivars, Mohamed Ben Bachir (MBB) and Hedab (HD), were growing under different concentrations of sea water salinity ( 10%, 30% and 60%) and the comparison plant control was also used.The results showed decreased continuously in plant length and yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…This instrument work on the principle of micro kjeldahl method of nitrogen analysis (Kjeldahl, 1883) [9] . [7] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument work on the principle of micro kjeldahl method of nitrogen analysis (Kjeldahl, 1883) [9] . [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Growth regulator having capable to improve metabolism and yield attributes of plants. Indole acetic acid and gibberellic acid significantly affects various attributes of plant growth and development (Gherroucha et al 2011) [8] . It is well known that the degree of leaf senescence is inversely proportional to cytokinin content, and exogenous application of kinetin helpful in increasing chlorophyll content as well (Sanaa et al 2006) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that plants pre-treated with IAA exhibited enhanced drought resistance (Almazroue, 2014). Foliar spraying with growth regulators (IAA and GA3 ) showed significant effect on plant, to the extent of reducing the hurt effect of salinity on the vegetative measurements and some physiological components of plant (Gherroucha et al, 2011). Shalaby and Kishk (1986) confirmed the increase of proline accumulation in the presence of growth regulators; stimulating hormones, especially quinine, regulate the synthesis and accumulation of dissolved sugars in growing plants in ss.m ab / prl.e, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The spraying of GA 3 , showed a significant effect on plant, in the extent of reducing the hurt effect of salinity on the vegetative measurements and some components of plant (Gherroucha et al, 2011). The application method of GA 3 had a stimulated effect on the adverse effect of salinity stress on the growth parameters and survival percentage for acclimatization stage (Darwesh and Mohamed, 2009).…”
Section: Introductionmentioning
confidence: 99%